КОМПЕНСАЦІЯ ПАРАМЕТРИЧНОЇ НЕСИМЕТРГЇ АСИНХРОННОГО ДВИГУНА ПРИ ЙОГО ЖИВЛЕННІ ВІД ЧАСТОТНО-РЕГУЛЬОВАНОГО ЕЛЕКТРОПРИВОДА - Чумачова , А.В.; Калінов , А.П. (Інститут електродинаміки НАН України, Київ, 2012)
The paper justificates the expressions to identify the corrective voltagefor compensation of the variable components of the induction motor active power and electromagnetic torque, which caused by stator phases asymmetry. Reference 1, table 1, figures 2.